Merry hell : the story of the 25th Battalion (Nova Scotia Regiment), Canadian Expeditionary Force 1914-1919 - Clements, Robert N., 1894- (University of Toronto Press, 2013)
Merry Hell is a captivating tale for those who enjoy stories of war and battle, and one that will entertain readers with Clements's richly colourful anecdotes and witty poems, none of which have been published before.